Improving Basic Cartwheel Movements Through Rubber Rope Media at Elementary School CIBOGO - Ahmad Fariz; Tedi Supriyadi; Anin Rukmana (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This research was conducted based on the problem of many students at elementary school CIBOGO who have not mastered the basic movements of floor gymnastics cartwheels, this research attempts to apply learning that can foster students’ interest and self-confidence in learning floor gymnastics cartwheels, the method used is to apply floor gymnastics cartwheel learning through rubber rope media. This research is a classroom action research with the research subjects of grade IV students of elementary school CIBOGO. The results of the study showed an increase in student learning outcomes after the implementation of learning through the rubber media from cycle I to cycle II. The results after implementing cycles I and II showed that student scores increased from the initial number of students who had completed only 17 students or 53.12% with the lowest score of 67.5. increased significantly to 28 students or around 87.5% of students who completed. And students who had not completed were 4 students or 12.5%. So it can be concluded that the method of learning floor gymnastics cartwheels through rubber rope media can improve student learning outcomes in learning physical education, health and sports, material floor gymnastics cartwheels.